Technical Efficiency Analysis of Sugar Cane Production in East Java - Wiwit Widyawati (HABITAT, 2020)
Having an important role as the main supplier of sugar cane in Indonesia that processed into sugar, so that East Java as a producer of sugar cane both with Ratoon Cane (RC) and Plant Cane (PC) must be supported by the government to be more productive and competitive. One of them is through increasing sugar cane yield through increasing technical efficiency. The purpose of this study is to analyze the level of technical efficiency in the use of sugar cane farming and identify the level of technical efficiency of farm households. The research location was determined purposively in Malang, Pasuruan, Lumajang, Bondowoso and Situbondo Regencies in July - December in 2018. Determination of respondents was carried out using the typical case sampling method. The technical efficiency of each farmer is carried out using a comparison of the actual production functions achieved by farmers using the frontier production function. The results showed the level of technical efficiency in sugar cane farming in wetland and dry land using RC and PC planting systems respectively averaged 89.44% and 99.80% so it was technically efficient.